Effects of Ion-Releasing Tooth-Coating Material on Demineralization of Bovine Tooth Enamel - Koji Kawasaki; Masaki Kambara (Hindawi Limited, 2014)
We compared the effect of a novel ion-releasing tooth-coating material that contained S-PRG (surface-reaction type prereacted glass-ionomer) filler to that of non-S-PRG filler and nail varnish on the demineralization of bovine enamel subsurface lesions. The demineralization process of bovine enamel was examined using quantitative light-induced fluorescence (QLF) and electron probe microanalyzer (EPMA) measurement. Ion concentrations in demineralizing solution were measured using inductively coupled plasma atomic (ICP) emission spectrometry and an ion electrode. The nail varnish group and the non-S-PRG filler group showed linear demineralization. Although the nail varnish group and the non-S-PRG filler group showed linear demineralization, the S-PRG filler group did not. Further, plane-scanning by EPMA analysis in the S-PRG filler group showed no changes in Ca ion distribution, and F ions showed peak levels on the surface of enamel specimens. Most ions in the demineralizing solution were present at higher concentrations in the S-PRG filler group than in the other two groups. In conclusion, only the S-PRG filler-containing tooth-coating material released ions and inhibited demineralization around the coating.